2017
DOI: 10.1111/phpp.12286
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Aloe sterols against UVB‐induced photoaging in hairless mice

Abstract: The dietary ingestion of Aloe sterols protected against chronic UVB damage in mouse skin, and our results suggest that Aloe sterols may prevent skin photoaging through the anti-inflammation and MMP regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…3). A fibroblast collagenase, MMP-13, is the key enzyme responsible for breaking down dermal components (31,32). Once the MMP-13 activation initiates degradation of fibrillary type I and III collagen, further processing is performed by MMP-3 and MMP-9 (23).…”
Section: Discussionmentioning
confidence: 99%
“…3). A fibroblast collagenase, MMP-13, is the key enzyme responsible for breaking down dermal components (31,32). Once the MMP-13 activation initiates degradation of fibrillary type I and III collagen, further processing is performed by MMP-3 and MMP-9 (23).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive components in A. vera have been reported to have antifungal, antiseptic, antiviral, antibacterial, anti-inflammatory, antioxidant, immuno-modulatory and wound healing properties 61,62 . Several studies also demonstrated beneficial effects of A. vera on UVB-induced damage [63][64][65] .…”
Section: Aloe Veramentioning
confidence: 96%
“…They have also been found to decrease the expression of MMP-2 and MMP-9, protecting collagen and the ECM from degradation, in UVB-irradiated hairless mice [ 47 ]. In addition, studies have showed that oral Aloe sterol may encourage the production of hyaluronic acid in human dermal fibroblasts [ 49 ]. Further studies are needed to determine the role of oral Aloe sterols and optimal daily allowance while accessing for supplementation health risks.…”
Section: Potential Future Nutraceuticalsmentioning
confidence: 99%